International trade in financial services : the NAFTA provisions - Nadakavukaren Schefer, Krista; Southern Methodist University. Institute of International Banking and Finance (The Hague ; Boston : Kluwer Law International, 1999)
This book examines the new and rapidly developing area of law relating to trade in finance services, with a particular focus on the rules contained in chapter 14 of the North America Free Trade Agreement (NAFTA).
At head of title: SMU Institute of International Banking and Finance, Dallas, Texas ... [et al.].
Includes bibliographical references (p. 415-440) and index.
aug10/05/13
Loans
Keywords: Financial services industry -- Law and legislation -- North America; Banking law -- North America; Free trade -- North America